2017
DOI: 10.1017/s0016756817000954
|View full text |Cite
|
Sign up to set email alerts
|

Use of electromagnetic radiation for potential forecast of earthquakes

Abstract: A forecast of an earthquake should identify the first stages of earthquake development: nucleation and stick-slip. We show that a forecast cannot be achieved by seismic measurements due to their high attenuation, but can be obtained by judicial filtering of electromagnetic radiation. Results show that electromagnetic radiation emitted from fractures (FEMR) during the early stages of an earthquake is less attenuated than seismic measurements due to the high frequencies involved, but could be cluttered by extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…One relevant property of rock samples is the increasing number of cracks before the main failure [ 7 , 8 , 54 , 69 ]. This means that the role of cracking and its electromagnetic signals correspond to a pre-failure feature that can be used as a forecast for major earthquakes [ 4 ]. On the other hand, it is known that the lithospherical surface deformation is a feature of the interseismic cycle which is observed in the middle of two large earthquakes [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One relevant property of rock samples is the increasing number of cracks before the main failure [ 7 , 8 , 54 , 69 ]. This means that the role of cracking and its electromagnetic signals correspond to a pre-failure feature that can be used as a forecast for major earthquakes [ 4 ]. On the other hand, it is known that the lithospherical surface deformation is a feature of the interseismic cycle which is observed in the middle of two large earthquakes [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…The first approach makes impossible the forecast of major earthquakes due to two main reasons: the vanishing seismic source information due to the attenuation of seismic waves [ 4 ] and, the interplay among different heterogeneous physical processes that make the rupture chaotic [ 5 ]. Despite this, it has been recently shown that any prediction should be done using multidisciplinary precursors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pulses emanating from FEMR sources have the shape as depicted in Fig. 12 which are "multiple single pulses" as opposed to EMR signals which are continuous in nature (Rabinovitch et al 2018;Das et al 2020). Furthermore, ANGEL-M is equipped with a second-order high-pass analog filter to refine the obtained signals and a "set trigger" option to set the signal-noise ratio of the incoming signals.…”
Section: Methodsmentioning
confidence: 99%
“…The generation of the fracture-induced electromagnetic radiation (FEMR) owes its existence to the incremental increase in stress subjected to the brittle rock bodies in the near surface of the Earth's crust. This phenomenon leads to the occurrence of fracturing in the rock bodies which, in turn, leads to the generation of FEMR pulses having a frequency range of MHz to kHz (Mallik et al 2008;Rabinovitch et al 2007Rabinovitch et al , 2017Rabinovitch et al , 2018Das et al 2020). The FEMR pulses emanate from microcracks/nanocracks present in the brittle rock bodies.…”
Section: Basics Of Fracture-induced Electromagnetic Radiation (Femr)mentioning
confidence: 99%
“…Rabinovitch et al have stated that the fracture-induced electromagnetic radiation has better strength than those obtained in the seismic measurements due to the less attenuation property of the fracture-induced EMR [116]. Fujinawa and Noda have presented a study of 13 electric field monitoring stations in Japan near earthquake zone and have discussed the progress in the use of electromagnetism for the earthquake prediction and earlier warning [117].…”
Section: Rocks and Brittle Materialsmentioning
confidence: 99%